2005
DOI: 10.1007/s10508-005-3119-5
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sexual Risk Behavior Change Among Sexually Transmitted Infection Clinic Patients

Abstract: Effective interventions to reduce sexually transmitted infection (STI) risk behaviors are most potent in the short term and are not uniformly effective for all people. The present study examined patterns of sexual behavior change among 238 men and 104 women who received risk reduction counseling in a public STI clinic and were followed for 9 months with a 1-year retrospective clinic chart abstraction for newly diagnosed STI. A two-stage, multivariate cluster analysis was performed on four risk behavior differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…This study presents one of the few longitudinal analyses of sexual behaviors among women in the US at elevated risk of HIV infection (24, 35, 36). We found that high-risk individual behaviors of exchange sex, unprotected anal intercourse and concurrent partnerships were common, each reported by approximately one-third of participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study presents one of the few longitudinal analyses of sexual behaviors among women in the US at elevated risk of HIV infection (24, 35, 36). We found that high-risk individual behaviors of exchange sex, unprotected anal intercourse and concurrent partnerships were common, each reported by approximately one-third of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Among urban, heterosexual women at elevated risk of HIV acquisition the reported one-year prevalence rates are higher, 38% for anal sex and 41% for exchange sex (22). The few studies that have assessed longitudinal patterns of sexual risk behaviors, particularly among women at elevated risk, have focused on adolescents (23) or have a small sample size (24). Thus, there is little information about how these specific sexual risk behaviors may change over time and what initial factors predict sustained patterns of engaging in a given risk behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These include noninjection risks such as sharing intranasal drug use equipment (Koblin et al, 2003) and binge drug use (Miller et al, 2006), and injection behaviors that incur heightened risk, such as transitioning between noninjection and injection drug use (Griffiths et al, 1992; Strang et al, 1992; Griffiths et al, 1994; Darke et al, 1994a, 1994b; Crofts et al, 1996; Irwin et al, 1996; Fuller et al, 2002; Abelson et al, 2006), assisting someone with injections or being a new intravenous drug user (Hagan et al, 2001; Vidal-Trecan et al, 2002; Wood et al, 2003; Roy et al, 2004; O’Connell et al, 2005; Fairbairn et al, 2006), and being a former but not current intravenous drug user (Friedman et al, 1995; Neaigus et al, 2001b). Additional sexual risk behaviors have also been identified, including the frequency of anal and vaginal sexual intercourse and whether the act was insertive or receptive (Benotsch et al, 1999; Hoffman et al, 2000), sex with other drug users (Neaigus et al, 2001a; Bravo et al, 2003; Roy et al, 2004; Purcell et al, 2006), having sex while under the influence of drugs (Celentano et al, 2006), having sex for an extended duration of time (Semple et al, 2009), having a lifetime history of a sexually transmitted disease (Hwang et al, 2000; Kalichman et al, 2005), and being sexually active following an HIV diagnosis (Campsmith et al, 2000; Aidala et al, 2006; Carrieri et al, 2006; Niccolai et al, 2006; Brewer et al, 2007). Finally, risks specific to the drug class being abused, including alcohol (Fitterling et al, 1993; Rasch et al, 2000; Stein et al, 2000; Rees et al, 2001; Kalichman et al, 2005; Raj et al, 2006), stimulants (Booth et al, 2000; Logan and Leukefeld, 2000; McCoy et al, 2004; Edwards et al, 2006; Volkow et al, 2007), and opioids (Sanchez et al, 2002; El-Bassel et al, 2003; Conrad et al, 2015) have also been associated with increased disease risk.…”
Section: Introductionmentioning
confidence: 99%
“…Additional sexual risk behaviors have also been identified, including the frequency of anal and vaginal sexual intercourse and whether the act was insertive or receptive (Benotsch et al, 1999; Hoffman et al, 2000), sex with other drug users (Neaigus et al, 2001a; Bravo et al, 2003; Roy et al, 2004; Purcell et al, 2006), having sex while under the influence of drugs (Celentano et al, 2006), having sex for an extended duration of time (Semple et al, 2009), having a lifetime history of a sexually transmitted disease (Hwang et al, 2000; Kalichman et al, 2005), and being sexually active following an HIV diagnosis (Campsmith et al, 2000; Aidala et al, 2006; Carrieri et al, 2006; Niccolai et al, 2006; Brewer et al, 2007). Finally, risks specific to the drug class being abused, including alcohol (Fitterling et al, 1993; Rasch et al, 2000; Stein et al, 2000; Rees et al, 2001; Kalichman et al, 2005; Raj et al, 2006), stimulants (Booth et al, 2000; Logan and Leukefeld, 2000; McCoy et al, 2004; Edwards et al, 2006; Volkow et al, 2007), and opioids (Sanchez et al, 2002; El-Bassel et al, 2003; Conrad et al, 2015) have also been associated with increased disease risk. Since all of these risks were identified after the development of the HRBS and RAB, they were not included in those assessments and are therefore not systematically queried or reliably used to determine infectious disease risk profiles for patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of sexual risk behaviour change among STI clinic patients Kalichman et al (2005) report on a cluster analysis of STI clinic patients which identified subgroups that differed on patterns of change in risk behaviour over the course of a 9-month follow-up after brief STI risk reduction counselling. Wechsberg et al (1998) had previously shown that identifying differential intervention outcomes for different subgroups of women may help inform future efforts to tailor and target behavioural interventions.…”
Section: Introductionmentioning
confidence: 99%